RESPON BIBIT GENERATIF TANAMAN DUKU (Lansium domesticum Correa) PADA BERBAGAI ORDO TANAH TERHADAP PEMUPUKAN NPK - Kartina AM (Jurnal Agroekoteknologi, 2009)
ABSTRACTA research was carried out to know response duku seedling on soil from various location to NPK fertilizer. The research was conducted in green house of BPSB TPH IX from January until April and arranged in Randomized Completely Block Design with Split Plot Design and to know NPK absorbtion to leaf meristem obtained through laboratory analysis. The result of research showed that response of duku seedling on soil from various locations to NPK fertilizer was tested not significant to all of parameters observed except to plant height accretion of NPK fertilizer.Key words: Duku (Lansium domesticum Correa), Seedling, NPK